Hubungan Mekanisme Koping Dengan Konsep Diri Pada Remaja Korban Cyberbullying - Hutabarat, Baby Bianca Angeline; Pasaribu, Jesika (STIKES Karya Husada Kediri, 2024)
Cyberbullying is a negative impact of using social media. The negative impacts of cyberbullying on victims include experiencing symptoms of depression, anxiety, psychosomatic problems, decreased performance at school, decreased self-esteem and even self-destruction. Adaptive coping mechanisms are crusial to prevent worse impacts of cyberbullying. This research was aimed to determine the relationship between coping mechanisms and self-concept in adolescent victims of cyberbullying. The research method was a correlative descriptive research design with the crosstab chi-square test. The sampling technique used purposive sampling as many as 116 students. Univariate analysis results: the majority of respondents were female (69.0%), adaptive coping mechanisms (60.3%), experienced heavy cyberbullying victimization (52.6%) and high self-concept (73.3%). The results of bivariate analysis using the chi-square test showed no significant relationship between coping mechanisms and self-concept in adolescent victims of cyberbullying (p-value 0.112). Research recommendation: adolescents maintain adaptive coping, get social support and improve nurses and teachers in preventive and promotive activities regarding cyberbullying.